PEMETAAN SOSIAL DAN IDENTIFIKASI PENGELOLAAN LAHAN OLEH MASYARAKAT DI KAWASAN HUTAN LINDUNG LIANG ANGGANG KALIMANTAN SELATAN - Lilis Sandari Agustina; Hamdani Fauzi; Hafizianor Hafizianor (Universitas Lambung Mangkurat, 2020)
Forest land management activities (occupational) is one of the destructive activities towards the utilization of forest resources. Destructive activities can damage the balance of the state of the forest. Management of protected forests that are not optimal by the government, raises the thinking of the community to manage forest land because the views of land are not utilized. The purpose of this study is to identify the extent and distribution of land that has been managed by the community. Analyze the way land is controlled by the community.Analyze the forms and activities of land management by the community and the causes of land management by the community. The community in obtaining land tenure in various ways, among others: obtaining part of the land when the division as cultivated land by the head of Padang in 1995, a small portion of which sold divided land so that the buyer got land ownership by buying it to the first manager and some rented land to the first manager. The forms of management of protected forest land in the North Landasan Ulin sub-district carried out by the community include: planting horticulture and vegetables with agroforestry systems, planting forestry and plantations as well as building non-permanent houses. The factors that cause the community to use protected forests in North Landasan Ulin Village are the causes of social aspects, supporting the community as farmers, views on Protected Forest areas in North Landasan Ulin Village that are not used, and suitable for land use, and from an economic perspective. personal because it is a migrant resident, the need to meet daily needs and the amount received. Keywords: Protection Forest; occupation; community; Agroforestry